(untitled) (University Arena, 2025)
Background. Within non-profile higher education, football stands out as one of the most highly regarded sports disciplines, consistently ranking among the top preferences of students at the University of Bucharest. Furthermore, students who have previously engaged in football at a competitive level, or those who demonstrate an advanced level of motor skills and sport-specific abilities, may be considered for selection to join the University of Bucharest Representative Football Team, hence the need to approach the selection process and the specific training in a more modern and objective manner. Objectives. This study aims to underscore the significance of assessing the initial stage of psychomotor development in prospective members of the University of Bucharest Representative Football Team. Furthermore, it seeks to emphasize the necessity and timeliness of integrating psychomotor evaluation as a complementary element within the selection process and the specific training. Methods. The participants in this study, totaling 20 male individuals, age between 19–21 years old, are first-year students enrolled in various faculties within the University of Bucharest. At the commencement of the 2024–2025 academic year, they expressed their intention to take part in the selection process for admission into the University’s Representative Football Team. In addition to the motor assessments specific to the discipline, the participants underwent psychomotor evaluation through the administration of four subtests drawn from the Second Edition of the Bruininks-Oseretsky Test of Motor Proficiency. Results. The four subtests selected from the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition, for the purposes of this study included Bilateral Coordination, Balance, Running Speed and Agility, and Strength. The results obtained from the subtests assessing Running Speed and Agility, Bilateral Coordination, and Balance, while relatively homogeneous, predominantly fell within the average range when compared to the specific sample. In contrast, the scores obtained in the Strength subtest were, in the majority of cases, above the average for the specific sample of participants in the assessment. Conclusion. The results obtained from the current research, despite being subject to certain limitations primarily related to the number of participants and the absence of the logistical resources required for the full implementation of the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition, affirm the significance and necessity of understanding the psychomotor profile of the students who are members of the University of Bucharest’s Representative Football Team.